Range extension and sexual dimorphism in Megabatrus caviceps Löbl (Coleoptera, Staphylinidae, Pselaphinae) - Yin, Zi-Wei; Li, Li-Zhen (Zootaxa, 2015)
Megabatrus caviceps Löbl, originally described from Kuatun, Fou-kien (= Guadun, Fujian), eastern China, is recorded from the Nanling Nature Reserve, Guangdong, southern China, ca. 550 km SW from the type locality. The female of this species is discovered and described for the first time. For comparative purposes, male diagnostic characters of M. caviceps are figured and supplementary description is provided. Some new data on this species’ biology are given.